1986
DOI: 10.1038/bjc.1986.39
|View full text |Cite
|
Sign up to set email alerts
|

Increased EGF receptors on human squamous carcinoma cell lines

Abstract: Summary Characterisation and quantitation of epidermal growth factor receptors (EGFR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
52
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(55 citation statements)
references
References 28 publications
(24 reference statements)
3
52
0
Order By: Relevance
“…Potentially, overexpression of either the growth factor or its receptor could contribute to the process of carcinogenesis. Reports in the literature have suggested that over-expression of the receptor protein may occur in several types of tumour (Neal et al, 1985;Hwang et al, 1986;Cowley et al, 1986), including those of the brain (Lieberman et al, 1985) and breast (Sainsbury et al, 1985). Whether the growth factor or its receptor are involved in carcinogenesis in man is as yet unclear.…”
mentioning
confidence: 99%
“…Potentially, overexpression of either the growth factor or its receptor could contribute to the process of carcinogenesis. Reports in the literature have suggested that over-expression of the receptor protein may occur in several types of tumour (Neal et al, 1985;Hwang et al, 1986;Cowley et al, 1986), including those of the brain (Lieberman et al, 1985) and breast (Sainsbury et al, 1985). Whether the growth factor or its receptor are involved in carcinogenesis in man is as yet unclear.…”
mentioning
confidence: 99%
“…Owing to its reported overexpression, the EGFR has been suggested to be a potential target for diagnosis (Soo et al, 1987;Divgi et al, 1991) or directed therapy of SCC (Harris, 1990;Ennis et al, 1991). Although several studies have indicated that the EGFR is overexpressed on human SCC, quantitation of the overexpression relies heavily on the study of SCC-derived cell lines in which the frequency of significant overexpression is very high (Cowley et al, , 1986. Most studies have relied upon cell lines which have been isolated under culture conditions unfavourable for the growth of normal keratinocytes (Easty et al, 1981).…”
mentioning
confidence: 99%
“…The EGFR is frequently, but not necessarily, overexpressed on SCC-derived cell lines (Wrann & Fox, 1979;Merlino et al., Cowley et al, 1984Cowley et al, , 1986Ozanne et al, 1986a;Prime et al, 1994) and tumours (Hendler & Ozanne, 1984;Gullick et al, 1986;Ozanne et al, 1986b;Derynck et al, 1987;Hendler et al, 1989;Ishitoya et al, 1989;Weichselbaum et al, 1989;Gullick, 1991;Gorgolis et al, 1992). Its gene, c-erbB (Downward et al, 1984), is located on chromosome 7pl2-14 and spans at least 10kb (Haley et al, 1987).…”
mentioning
confidence: 99%
“…Many human cancers of epithelial origin express high numbers of EGF receptors and are stimulated by activation of the receptor via a transforming growth factor-α (TGF-α)/EGF receptor autocrine loop (Ozanne et al, 1986;Cowley et al, 1986;Ishitoya et al, 1989;Hendler and Ozanne, 1984). The increased receptor levels are associated with poor clinical prognosis in patients with cancers of the bladder (Neal et al, 1985), breast , and lung (Veale et al, 1987) and others.…”
mentioning
confidence: 99%